Tourism-led growth or economy-driven tourism growth in Southeast Asian countries - Fei Fan; Van-Trung Ha (Humanities & Social Sciences Communications)
Abstract The relationship between tourism and economic development in the Association of Southeast Asian Nations (ASEAN) countries has long been debated, particularly concerning the tourism-led growth and economy-driven tourism growth hypotheses. This study investigates these competing perspectives, analyzing how tourism and economic growth influence each other across 11 ASEAN nations using panel causality tests and structural equation modeling. Findings reveal that economic growth promotes tourism development in all eleven ASEAN states. However, in larger economies, tourism substantially impacts economic growth, while economic development has a lesser influence on tourism. In less-developed ASEAN countries, neither hypothesis shows definitive evidence. The study highlights tourism’s significant role in driving economic growth, particularly in more developed nations, and encourages sustainable tourism practices in less-developed economies. This research contributes to the ongoing discussion on tourism’s dual role in shaping economic outcomes within the ASEAN region, offering insights for policymakers and tourism industry stakeholders.